2010
DOI: 10.2353/ajpath.2010.090503
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortus Induces the Secretion of Proinflammatory Mediators from Glial Cells Leading to Astrocyte Apoptosis

Abstract: Central nervous system (CNS) invasion by bacteria of the genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 60 publications
7
97
0
Order By: Relevance
“…are mainly adapted to establish chronic infections in macrophages (3). Thus, our results suggest that osteoblasts do not constitute a survival niche for long-term Brucella persistence in osteoarticular localization and go along with the fact that B. abortus can induce apoptosis of cell types other than macrophages (13,15). We hypothesize that apart from resident macrophages, other monocytes/macrophages could be attracted to the site of osteoarticular infection through MCP-1 secretion mediated by B. abortus-infected osteoblasts, increasing the likelihood of finding a replicative niche.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…are mainly adapted to establish chronic infections in macrophages (3). Thus, our results suggest that osteoblasts do not constitute a survival niche for long-term Brucella persistence in osteoarticular localization and go along with the fact that B. abortus can induce apoptosis of cell types other than macrophages (13,15). We hypothesize that apart from resident macrophages, other monocytes/macrophages could be attracted to the site of osteoarticular infection through MCP-1 secretion mediated by B. abortus-infected osteoblasts, increasing the likelihood of finding a replicative niche.…”
Section: Discussionmentioning
confidence: 87%
“…abortus-mediated apoptosis has been reported for a variety of cells, including astrocytes and hepatocytes (13,15). In particular, it has been demonstrated that astrocyte apoptosis induced by B. abortus infection involves caspase activation (15).…”
Section: B Abortus Invades and Multiplies In Primary Mouse Osteoblasmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this last property we found that heat-killed B. abortus (HKBA) can stimulate cytokine and MMP-2 production by human FLS, clearly indicating that these FLS responses may be elicited by one or more structural components of B. abortus. Since Brucella lipoproteins induce the production of proinflammatory cytokines in several cell types (13,14,59) and can also induce MMP-9 production by human monocytes (41), we hypothesized that such lipoproteins could also stimulate the production of cytokines and MMP-2 in FLS. Using Omp19 as a model Brucella lipoprotein, we found that its lipidated version (L-Omp19), but not its unlipidated form, induced the production of proinflammatory cytokines and MMP-2 by FLS.…”
Section: Discussionmentioning
confidence: 99%
“…7, FLS stimulated with HKBA produced elevated levels of GM-CSF, IL-6, IL-8, and MCP-1, in general in a dose-dependent fashion, indicating that the secretion of these factors can be stimulated by a structural component of B. abortus. Since we previously found that B. abortus lipoproteins induce cytokine, chemokine, and MMP secretion in different cell types (13,14,41,59), we hypothesized that lipoproteins could also mediate such effects in FLS.…”
Section: Brucella Abortus-induced Secretion Of Mmp-2 and Cytokines Inmentioning
confidence: 99%